Hypertension : Experimental and clinical pharmacological studies - Leary, William, Peregrine, Pepperrell (My University, 1985)
The publications forming this submission cover two broad fields. A series of papers deal with experimental hypertension ; possible roles for angiotensin and prostanoid substances in the pathogenesis of hypertension were investigated. The results indicated that the capacity of kidney to inactivate angiotensin II could be quite profoundly altered by inducing hypertension using the one and two-clip Goldblatt methods or by altering the sodium chloride content of the diet.
A thesis submitted to the Faculty of Medicine, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Science (Medicine).
Keywords: Hypertension; Pharmacology, Clinical; Biomarkers